On Accurately Resolving Detonation Dynamics by Adaptive Finite Volume Method on Unstructured Grids (Communications in Computational Physics, 2020)
Long time simulations are needed in the numerical study of the Zeldovich-Neumann-Döring model, in which the quality resolving the dynamics of the detonation front is crucial. The numerical error introduced from the inappropriate outflowboundary condition and the mesh resolution are two main factors qualitatively affecting the dynamics of the detonation front. In this paper we improve the numericalframework in [15] by introducing the Strang splitting method and a new $h$-adaptivemethod with a feature based $a$ $posteriori$ error estimator. Then a cheap numerical approach is proposed to sharply estimate a time period, in which the unphysical influence on the detonation front can be avoided effectively. The sufficiently dense meshresolution can be guaranteed around the detonation front and in the reaction zoneby the proposed $h$-adaptive method. The numerical results show that the proposedmethod is sufficiently robust even for long time calculations, and the quality dynamicsof the detonation can be obtained by the proposed numerical approach.
Keywords: Reactive Euler equations; Strang splitting scheme; $h$-adaptive methods; subsonic outflow boundary; ZND model.